The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.sbi.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to RNA structure prediction, analysis, and design

Abstract: RNA molecules are important cellular components involved in many fundamental biological processes. Understanding the mechanisms behind their functions requires RNA tertiary structure knowledge. While modeling approaches for the study of RNA structures and dynamics lag behind efforts in protein folding, much progress has been achieved in the past two years. Here, we review recent advances in RNA folding algorithms, RNA tertiary motif discovery, applications of graph theory approaches to RNA structure and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 77 publications
1
101
0
Order By: Relevance
“…3 We created plots using the AssayToolbox library for R [39,40]. We generate all random graphs using a generator for dynamic graphs 4 derived for vertex combination.…”
Section: Evaluation Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…3 We created plots using the AssayToolbox library for R [39,40]. We generate all random graphs using a generator for dynamic graphs 4 derived for vertex combination.…”
Section: Evaluation Setupmentioning
confidence: 99%
“…3 http://www.cbs.tu-darmstadt.de/streAM-Tg.tar.gz. 4 https://github.com/BenjaminSchiller/DNA.datasets the choice of MD integration step lengths as well as trajectory granularity.…”
Section: Runtime Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Liang and Schlick [47,48] systematically assessed existing RNA tertiary structure prediction methods and found that the accuracy is greater than 6.0 Å for most RNAs (50-130 nt), with a mean RMSD of 20 Å. Also, existing RNA tertiary structure prediction methods are mostly not automated, requiring human interaction for further manual adjustments to optimize the generated structures.…”
Section: Rna Secondary Structure Predictionmentioning
confidence: 99%